Procedural Status of an Expert in Criminal Proceedings - Pedos, Yu. V. (Вісник Харківського національного університету внутрішніх справ, 2025)
The provisions of the Criminal Procedure Code of Ukraine and the Law of Ukraine “On Forensic Expertise” establish the legal status of an expert as a participant in criminal proceedings, which is the most important legal guarantee of the objectivity and comprehensiveness of expert research. A detailed study of the content of these regulations indicates that there are discrepancies and inaccuracies in the definitions and wording of certain provisions, which does not contribute to the unambiguousness of their understanding. Based on the results of the study of the provisions of current legislation, scientific opinion and practice of application of legislative provisions regulating the legal status of an expert as a participant in criminal proceedings, the author identifies problematic issues and formulates proposals for improving criminal procedure legislation in this area. In particular, it is proposed to amend and supplement the provisions of certain paragraphs of Article 69 of the Criminal Procedure Code of Ukraine, setting out their content as follows: para. 5, part 3 – “to ask questions relating to the subject and objects of the study to the participants of the relevant procedural action”; para. 6(3) – “to receive remuneration for the work performed and reimbursement of expenses related to the examination and summons to provide explanations or testimony within a reasonable time, if the examination is not the official duty of the person involved as an expert”; clause 6(5) – “to immediately notify the person who engaged him or her or the court that commissioned the expert examination of the impossibility of conducting the examination due to the lack of necessary knowledge or without the involvement of other experts”; clause 7(5) – “to file a petition to the person who appointed the expert examination or the court that commissioned it, if there is a doubt about the content and scope of the assignment, its clarification, involvement of other experts or to notify of the impossibility of conducting the examination according to the questions posed to him or her”.